Training on Optimizing Sirekap Technology in Vote Counting and Recapitulation KPPS TPS 04 Urban Village Panancangan - Suryasuciramdhan, Arfian; Hakim, Cecep Abdul; Putra, Dias Suminta Suria; Permatasari, Diah; Amyati, Amyati; Priatna, Achmad Nashrudin (Asian Journal of Community Services, 2024)
One of the innovations implemented by the Indonesian General Election Commission (KPU) is the Recapitulation Information System (SIREKAP), a digital application designed to support the vote counting and recapitulation process directly from polling stations. This training aims to analyze the impacts and benefits of using SIREKAP technology in elections, as well as the challenges faced in its implementation. Training results show that SIREKAP increases the speed of the recapitulation process, reduces the potential for human error, and strengthens the accountability of election results. The method of implementing community service activities is carried out in five ways, Socialization of KPU About SIREKAP Application, Demonstration Stage of SIREKAP KPU Application to KPPS Officers, Implementation Stage of SIREKAP KPU Application to KPPS Officers, Implementation of KPPS Members of TPS 04 Vote Calculation and Recapitulation Results, Evaluation of KPPS TPS 04 Vote Calculation and Recapitulation Results.